Characterization of AI-2/LuxS quorum sensing system in biofilm formation, pathogenesis of Streptococcus equi subsp. zooepidemicus - Xie, Honglin; Zhang, Riteng; Guo, Ruhai; Zhang, Yining; Zhang, Jingya; Li, Hui; Fu, Qiang; Wang, Xinglong (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococcus equi subsp. zooepidemicus (SEZ) is an opportunistic pathogen of both humans and animals. Quorum sensing (QS) plays an important role in the regulation of bacterial group behaviors. The aim of this study was to characterize the LuxS in SEZ and evaluate its impact on biofilm formation, pathogenesis and gene expression. The wild-type SEZ and its LuxS mutant (ΔluxS) were examined for growth, biofilm formation, virulence factors, and transcriptomic profiles. Our results showed that LuxS deficiency did not affect SEZ hemolytic activity, adhesion or capsule production. For biofilm assay demonstrated that mutation in the luxS gene significantly enhances biofilm formation, produced a denser biofilm and attached to a glass surface. RAW264.7 cell infection indicated that ΔluxS promoted macrophage apoptosis and pro-inflammatory responses. In mice infection, there was no significant difference in mortality between SEZ and ΔluxS. However, the bacterial load in the spleen of mice infected with ΔluxS was significantly higher than in those infected with SEZ. And the pathological analysis further indicated that spleen damage was more severe in the ΔluxS group. Moreover, transcriptomics analysis revealed significant alterations in carbon metabolism, RNA binding and stress response genes in ΔluxS. In summary, this study provides the first evidence of AI-2/LuxS QS system in SEZ and reveals its regulatory effects on biofilm formation, pathogenicity and gene expression.